Uporaba tehnologij v izobraževanju na daljavo - Debevc, Matjaž (Uporabna informatika (Ljubljana), 2001)
Digital media an computer tecnologies are emerging in education today, offering new means of content delivery and communication. In this paper we arefirst giving an overview of such technologies especially regardong distance education. Beside classification according to technical generations we are also providing discrimination to synchronous and asynchronous educational technologies. Second part of the paper introduces the conceptual model of a hypermedia classroom, developed in the European Tempus project DETECH, incorporating traditional audio-visual presentation technology, group videoconferencing facilities, Web interaction equipment (whiteboards), elements of a digital video studio for lecture recording and high speed local network with Internet connection. A variety of educational services can be offerd in such enhanced classroom, but on the other hand it can also be used for conducting various didactical experiments.
Keywords: Evropska unija; izobraževanje na daljavo; modeli; pripomočki